(untitled) (Journal of Humanitarian and Applied Sciences, 2023)
This study examines the reasons that led to the inadequate level of academic achievement for students of the Department of Geography at the College of Arts and Sciences / Qasr Alakhyar, which is one of the colleges affiliated to the University of Almergib. The final results of the students (first round) showed that the failure field recorded the highest value of the total results of the students when it reached (49.3%), considering that these results are only a reflection and measure of the level of achievement of students. The study used the views of faculty teaching members and students through two questionnaire models in ordering these reasons from the most influential to the least influential, after they were framed as weighted paragraphs (4 to 1), with the aim of extracting weighted mean and percentage weight per paragraph. Statistical procedures showed an absolute agreement of faculty members’ opinions that the total and complete dependence on the professor of the course in preparing and delivering lectures, being the main and only source of the scientific material, is the most prominent reason that contributes to the low level of academic achievement among students, where the weighted average reached (4) and a percentage of (100%). While the extrapolation of the students’ opinions showed that the Corona pandemic was the first cause of the frustration and confusion that prevailed in the two years (2020-2021), and thus the academic level of students studying in these two years specifically declined from their point of view. However, it is indicated that it is not acceptable to say that this reason is what they contributed in the low academic achievement of previous years, because this epidemic appeared late and that the questionnaire was applied to students of these two years only, and the students as well agreed on this paragraph with a weighted mean (4) and a percentage of (100%). The study recommended that the necessary steps be taken to raise the quality of the teaching staff member and students in the educational process to ensure the quality of its outputs.